2014
DOI: 10.1016/j.jmb.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Sequence of Tyrosine Hydroxylase Is a Conformationally Versatile Motif That Binds 14-3-3 Proteins and Membranes

Abstract: Tyrosine hydroxylase (TH) catalyzes the rate limiting step in the synthesis of catecholamine neutrotransmitters, and a reduction of TH activity is associated with several neurological diseases. Human TH is regulated, among other mechanisms, by Ser19-phosphorylation-dependent interaction with 14-3-3 proteins. The N-terminal sequence (residues 1-43), which corresponds to an extension to the TH regulatory domain, also interacts with negatively charged membranes. By using X-ray crystallography together with molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…21 and this work). Experimental20 and computational28 studies on TH-(1-43) peptide revealed an increased α-helical content in this stretch when bound to negatively charged membranes, a change that may be less easy to observe in the full-length enzyme, a tetramer of 497 amino acids per subunit. Many other protein-membrane interactions appear to involve amphipathic helices3, and altogether, our results support a model in which hTH1 associates to the membrane via the α-helical N-terminus and aggregates through inter-tetramer cross-β interactions involving the catalytic domains (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…21 and this work). Experimental20 and computational28 studies on TH-(1-43) peptide revealed an increased α-helical content in this stretch when bound to negatively charged membranes, a change that may be less easy to observe in the full-length enzyme, a tetramer of 497 amino acids per subunit. Many other protein-membrane interactions appear to involve amphipathic helices3, and altogether, our results support a model in which hTH1 associates to the membrane via the α-helical N-terminus and aggregates through inter-tetramer cross-β interactions involving the catalytic domains (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have determined the interaction of TH and its N-terminal sequence with negatively charged membranes202128, however the effect of this interaction on membrane integrity has not been investigated. We assessed the effect of TH on the integrity of negatively charged membranes, using purified recombinant hTH1, which is the most abundant splicing isoform of TH in brain and adrenal medulla17, and measuring the fluorescence of released 8-aminonaphtalene-1,3,6-trisulphonic acid, disodium salt (ANTS) from LUVs, which will also be referred here to as liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…57,60 An individual (ND27637) with Lennox-Gastaut syndrome and a de novo p.Asp129Glu variant is present in the Epi4K-EPGP dataset. 4 The Asp129 residue is also located within the 14-3-3g binding groove ( Figure 1) and plays an important role in determining the orientation of the phosphorylated peptides.…”
mentioning
confidence: 99%
“…Lines indicate protein-glycopeptide hydrogen bonds (Left), and blue mesh indicates the initial Fo-Fc map, calculated before glycopeptide addition, contoured at 2.9 σ (14-3-3γ) or 2.5 σ (14-3-3β/α) (Right). (F) Overlay of 14-3-3γ-glycopeptide (from D) and 14-3-3γphosphopeptide from tyrosine hydroxylase (magenta protein, red phosphopeptide; PDB 4J6S)(75). O-GlcNAc and O-phosphate moieties are highlighted by transparent surfaces.…”
mentioning
confidence: 99%